Arqueología de la arquitectura en el oppidum oretano de El Cerro de las Cabezas (Valdepeñas, Ciudad Real) : los bastiones de la puerta S - del Reguero González, Jorge (Access archaeology., 2021)
This book focuses on the two bastions that make up the south gate of the Iberian oppidum of Cerro de las Cabezas (Valdepeñas, Ciudad Real). It comprises two defensive constructions whose internal space fulfilled a socioeconomic function related to the storage of cereal.